2017
DOI: 10.22159/ajpcr.2017.v10i12.20394
|View full text |Cite
|
Sign up to set email alerts
|

Leptin and Adiponectin Levels of Asthmatic Iraqi Children in Hilla Province

Abstract: Objective: To assess the serum leptin and adiponectin in Iraqi children with asthma and compare it with healthy controls in Hilla province. Methods:Leptin and adiponectin were measured in 100 children; 60 newly diagnosed with asthma and 40 non-asthmatic children with a comparable age and sex were enrolled in this study. Asthmatic children subdivided into two groups; 30 patients in each group (obese and non-obese). The age of patients and control ranged between 2 and 12 years. The study was conducted in the Dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
(40 reference statements)
0
1
0
Order By: Relevance
“…Our included asthmatic patients were mostly males. Studies found a higher frequency of asthma in males than females [ 66 , 67 ]. Different patterns of lung function abnormalities in males and females existed due to different pattern of lung growth and fat deposition [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our included asthmatic patients were mostly males. Studies found a higher frequency of asthma in males than females [ 66 , 67 ]. Different patterns of lung function abnormalities in males and females existed due to different pattern of lung growth and fat deposition [ 7 ].…”
Section: Discussionmentioning
confidence: 99%